Studi Kewirausahaan dalam Pariwisata Olahraga: Analisis Bibliometrik - Ni Putu Erna Surim Virnayanthi; I Made Candiasa; I Gede Ratnaya; Ni Ketut Widiartini; Desak Putu Parmiti (Jurnal Penelitian Pendidikan IPA, 2024)
Bibliometric analysis provides valuable insights into developing entrepreneurial aspects in sports tourism. This study explores key research trends and themes in the intersection of sports tourism and entrepreneurship. The analysis of 200 articles using the keyword "entrepreneurial in sport tourism" reveals significant contributions to understanding sustainability, sports entrepreneurship, and adopting entrepreneurial behavior in developing countries. The study highlights the importance of considering sustainability in sports tourism development, identifying key areas in sports entrepreneurship, and understanding institutional factors influencing entrepreneurial opportunities. Additionally, the research emphasizes the role of entrepreneurial intentions in shaping tourism business activities, particularly in surf tourism. The findings suggest a gap in research linking tourism entrepreneurs with sports tourism and its impact, presenting opportunities for future research to bridge this gap and contribute to a more comprehensive understanding of the entrepreneurial landscape in sports tourism.